Extensive antimicrobial resistance mobilization via multicopy plasmid encapsidation mediated by temperate phages. (28th July 2020) - Rodríguez-Rubio, Lorena; Serna, Carlos; Ares-Arroyo, Manuel; Matamoros, Bosco R; Delgado-Blas, Jose F; Montero, Natalia; Bernabe-Balas, Cristina; Wedel, Emilia F; Mendez, Irene S; Muniesa, Maite; Gonzalez-Zorn, Bruno
Abstract: Objectives: To investigate the relevance of multicopy plasmids in antimicrobial resistance and assess their mobilization mediated by phage particles Methods: Several databases with complete sequences of plasmids and annotated genes were analysed. The 16S methyltransferase gene armA conferring high-level aminoglycoside resistance was used as a marker in eight different plasmids, from different incompatibility groups, and with differing sizes and plasmid copy numbers. All plasmids were transformed into Escherichia coli bearing one of four different lysogenic phages. Upon induction, encapsidation of armA in phage particles was evaluated using qRT–PCR and Southern blotting. Results: Multicopy plasmids carry a vast set of emerging clinically important antimicrobial resistance genes. However, 60% of these plasmids do not bear mobility (MOB) genes. When carried on these multicopy plasmids, mobilization of a marker gene armA into phage capsids was up to 10000 times more frequent than when it was encoded by a large plasmid with a low copy number. Conclusions: Multicopy plasmids and phages, two major mobile genetic elements (MGE) in bacteria, represent a novel high-efficiency transmission route of antimicrobial resistance genes that deserves further investigation.